Inverse vulcanization induced oxygen modified porous polysulfides for efficient sorption of heavy metals - Lyu, Shiqi; Zainal Abidin, Zurina; Yaw, Thomas Choong Shean; Gunam Resul, Mohamad Faiz Mukhtar (Springer, 2024)
The applications of polysulfides derived from natural plant oil and sulfur via the inverse vulcanization in the removal of heavy metals from aqueous solutions suffered from their low porosity and scarce surface functionality because of their hydrophobic surfaces and bulk characteristics. In this study, polysulfides from sulfur and palm oil (PSPs) with significantly enhanced porosity (13.7–24.1 m2/g) and surface oxygen-containing functional groups (6.9–8.6 wt.) were synthesized with the optimization of process conditions including reaction time, temperature, and mass ratios of sulfur/palm oil/NaCl/sodium citrate. PSPs were applied as sorbents to remove heavy metals present in aqueous solutions. The integration of porosity and oxygen modification allowed a fast kinetic (4.0 h) and enhanced maximum sorption capacities for Pb(II) (218.5 mg/g), Cu(II) (74.8 mg/g), and Cr(III) (68.4 mg/g) at pH 5.0 and T 298 K comparing with polysulfides made without NaCl/sodium citrate. The sorption behaviors of Pb(II), Cu(II), and Cr(III) on PSPs were highly dependent on the solution pH values and ionic strength. The sorption presented excellent anti-interference capability for the coexisting cations and anions. The sorption processes were endothermic and spontaneous. This work would guide the preparation of porous polysulfides with surface modification as efficient sorbents to remediate heavy metals from aqueous solutions.